Comparison of underwater and conventional endoscopic mucosal resection for removing sessile colorectal polyps: a propensity-score matched cohort study - Chien, Hsu-Chih; Uedo, Noriya; Hsieh, Ping-Hsin (Endoscopy International Open, 2019)
Background and study aims Endoscopic mucosal resection (EMR) is a standard method for removing sessile colorectal polyps ≥ 10 mm. Recently, underwater EMR (UEMR) has been introduced as a potential alternative. However, the effectiveness and safety of UEMR compared with conventional EMR is un clear. Patients and methods In this 1:1 propensity score (PS) matched retrospective cohort study, we compared the en bloc resection rates, procedure time, intraprocedural and delayed bleeding rates, and incidence of muscle layer injury. We also performed subgroup analyses by sizes of polyps (< 20 mm and ≥ 20 mm).Results Among 350 polyps in 315 patients from August 2012 to November 2017, we identified 121 PS-matched pairs. Mean polyp size was 16.8 mm. With similar en bloc resection rates (EMR: 82.6 % vs. UEMR: 87.6 %, rate difference: 5.0, 95 % confidence interval [95 % CI]: – 4 to 13.9 %), UEMR demonstrated a shorter resection time (10.8 min vs. 8.6 min, difference: – 2.2 min, 95 % CI: – 4.1 to – 0.3 min) and a lower intraprocedural bleeding rate (15.7 % vs. 5.8 %, rate difference: – 9.9 %, 95 % CI: – 17.6 to – 2.2 %). Incidence of delayed bleeding and muscle layer injury were low in both groups. For polyps < 20 mm, effectiveness and safety outcomes were similar in both groups. For polyps ≥ 20 mm (42 PS-matched pairs), the UEMR group has a comparable en bloc resection rate with shorter procedure time and superior safety outcomesConclusions UEMR achieved an en bloc resection rate comparable to conventional EMR with less intraprocedural bleeding and a shorter procedure time.